The social media use of African terrorist organizations: a comparative study of Al-Qaeda in the Islamic Maghreb, Al-Shabaab and Boko Haram - (:unkn) unknown (My University, 2021)
The objective of this qualitative study is to raise awareness of the online presence of al-Qaeda in the Islamic Maghreb (AQIM), al-Shabaab and Boko Haram by analyzing and comparing their social media activities. The decision that the above-mentioned terrorist organizations shall be selected for inclusion was based on the fact that (I.) they are active in Africa, (II.) they are currently or affiliated with three of the deadliest international terrorist groups in the continent and (III.) they use social media in order to achieve their goals. I conclude that social media is used by all three of the studied terrorist organizations with special attention devoted to mainstream social media platforms, namely Twitter, YouTube and-to a lesser extent-Facebook. Additionally, AQIM, al-Shabaab and Boko Haram seem to have primarily used social media for propaganda purposes, although it was also utilized as a recruitment tool, albeit to varying degrees. Finally, I believe social media can also be used for coordination and funding by the studied terrorist groups; although the small amount of publicly accessible evidence entails qualitative problems, indicating the fact there is room for further research.
Keywords: African Research